Random blood sugar levels and pseudocholinesterase levels their relevance in organophosphorus compound poisoning - Rao, Ramchander; Bala Raju, G. (International Journal Of Community Medicine And Public Health, 2016)
Background: Most of the organophosphates used as the insecticides inhibit both pseudocholinesterase and acetylcholinesterase. Estimation of erythrocyte cholinesterase (acetylcholinesterase) is theoretically preferred, since it would indicate the degree of inhibition of synaptic cholinesterase (also acetyle-cholinesterase). Estimation of plasma cholinesterase (pseudo cholinesterase) has an advantage because the measurement is simpler and more accurate than estimation of erythrocyte cholinesterase. Methods: We studied fifty cases of organophsphorus poisoning directly admitted in acute medical care of Osmania General Hospital, Hyderabad, India. Results: Out of fifty patients 26% of the patients had mild depression of serum pseudo cholinesterase levels and 42% of patients had moderate depression of serum cholinesterase levels and 32% of patients showed severe depressions of cholinesterase levels. Mortality rates of 26% were observed in our study, 6% of the patients required ventilatory support and two patients (4%) developed intermediate syndrome. Respiratory paralysis was the major cause of death. Conclusions: Hyperglycemia at admission correlates with depression of pseudo cholinesterase levels in organophosphorus poisoning. Random blood sugar levels of >200 mg/dl at admission and depression in pseudocholinesterase levels <1000 U/L (p<0.005) are reliable parameters to predict mortality and ventilator requirement in organophosphorus poisoning.